Effect of rearing conditions on astaxanthin accumulation in the white shrimp Penaeus vannamei (Boone, 1931) - Quintana-López,Anayeli (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2019)
ABSTRACT Astaxanthin is an essential micronutrient that regulates shrimp physiology, acting as a free radical scavenger, increasing stress resistance, and enhancing the immune response, improving growth and survival in farm-raised organisms. Despite this, accumulation of astaxanthin has not been evaluated regarding rearing conditions of shrimp. Thus, this study aimed to assess the effect of rearing conditions (extensive vs. hyperintensive) in the accumulation of astaxanthin in tissues of shrimp Penaeus vannamei, using wild juveniles as a reference of the levels of astaxanthin present in the natural environment. The main oxycarotenoid found was astaxanthin, which was mostly accumulated in hepatopancreas (>90%) in esterified form, while mostly free astaxanthin was found in exoskeleton and muscle (<60%). Comparing wild and reared shrimp, the content of esterified astaxanthin was significantly higher in the hepatopancreas of shrimp reared under extensive conditions (191.45 ± 23.08 μg g−1) followed by wild shrimp (144.08 ± 13.92 μg g−1), while low values (3 ± 1 μg g−1) were found in shrimp reared under hyper-intensive conditions. Astaxanthin levels found in farm-raised shrimp were not explained by commercial feeds, since no astaxanthin (only traces of its chemical precursor p-carotene), was found in the six different commercial feeds analyzed for rearing shrimp. Thus, the results may be explained by primary productivity (i.e., phytoplankton) that is consumed as natural food by shrimp in the ponds of farming systems, or by the effect of specific rearing conditions on the microbiota associated with carotenogenesis in the gut of shrimp. In any case, commercial feeds should fulfill all nutritional requirements for shrimp, particularly under stressful conditions as it occurs in hyper-intensive farming.